A new species of Euptychia Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae: Satyrini) from Mount Roraima, Guyana - Nakahara, Shinichi; Fratello, Steven A.; Harvey, Donald J. (Zootaxa, 2014)
A new nymphalid species in the subtribe Euptychiina, Euptychia roraima Nakahara, Fratello & Harvey n. sp., is described from Mount Roraima, Guyana. Both internal and external morphology of E. roraima are compared against several Euptychia species and the relationship between E. roraima and congeners is briefly discussed. A strong case is put forth for further and extensive exploration of the Pantepui region concerning its poorly known butterfly fauna.